Developing flexibility for combat sports athletes - Emerson Franchini (Universidad de León, 2021)
The range of motion of a joint is extremely important in combat sports, especially when there is a need to execute a certain motor gesture with maximum range of movement, as in throwing techniques such as uchi-mata in judo, certain types of guards in Brazilian jiu-jitsu or the high kicks common in a variety of striking combat sports. Therefore, in this chapter, we will discuss the elements related to flexibility response during training sessions or combat sports competitions, flexibility tests commonly used for these athletes, and the monitoring and control of the evolution of flexibility in athletes. We will also present the means and methods used for the development of flexibility and longitudinal studies on the development of flexibility in combat sports athletes. Finally, this chapter supports based on the evidence the inclusion of flexibility development within training sessions is an important consideration to maximize performance and other physical capabilities that may be affected both acutely or in the long-term by flexibility.